Enhancing Service Efficiency in Peruvian Automotive Workshops through the Integration of SMED, KANBAN, and TPM: A Lean-Based Empirical Study - Montes Cabrera, Abdel Farid (2025)
The automotive industry in Peru is a key sector of the economy, with steady growth in vehicle sales, leading to increased demand for maintenance services. However, auto repair shops face critical challenges such as delivery delays, post-service complaints, and inefficient resource management due to unplanned mechanical failures, prolonged setup times, and stockout issues. This study proposes a model based on TPM, SMED, and Kanban. TPM, through preventive and autonomous maintenance, aims to reduce unplanned failures and increase equipment availability. SMED addresses the reduction of setup times by standardizing processes. Kanban improves inventory management using boards and cards that optimize turnover and reduce stockouts. Simulations were conducted using Arena software, and statistical validations, including Kolmogorov-Smirnov and Chi-square tests, were applied to analyze time distributions with Input Analyzer. Kanban was validated through a baseline and improved model using a pilot test with Kanban boards and cards, along with Arena software simulation, while TPM and SMED were evaluated with joint simulations using Input Analyzer, ensuring 95% confidence intervals. The results show an increase in service level from 82.67% to 92.72%, surpassing industry standards and confirming the model’s effectiveness in improving operational efficiency. This approach is replicable and contributes to the competitive development of the automotive sector, enhancing customer satisfaction in repair shops in emerging markets.